DIMENSI KEPEMIMPINAN TRANSFORMATIF ERA DISRUPSI PERSPEKTIF MANAJERIAL BIROKRASI: DIMENSI KEPEMIMPINAN TRANSFORMATIF - Umam, Muhamad Khoirul (AL-WIJDÃƒÂN: Journal of Islamic Education Studies, 2019)
Changes that occur in management have an impact on competitive regional development towards global competition, both from national formal institutions and non-formal institutions. So this led to the birth of a new leadership model with a more innovative, creative, transformative, and continuously sustainable strategy. Because of the vast scope of management, the social community, government bureaucracy, organization and world government. The era of disruption makes managerial leadership required to be present and appear in the treasury of change or extinction in civilization. It must also be seen that a leader must also be able to see extreme conditions and situations in making decisions and policies that are in accordance with the leadership style applied, and situational leadership must also be coated with a collaborative leadership model and the type of leadership that will apply it to the political context also needs to be refined and put into the context of the bureaucracy or organization. So that raises questions about how the managerial bureaucracy seeks to draw a view of the dimensions of Islamic transformative leadership by presenting a model of transformative leadership in the form of superiority and managerial characteristics of the bureaucracy that is seen from the prophetic values ​​and views of the Qur'an. To answer this research question, researchers collected data through documentation methods, then after the data was collected, analyzed through content analysis and critical analysis. So this study produced an alternative offer that is modeling Islamic transformative leadership that intersects with the model of Idealized Influence (Inspiration), Inspirational Motivation, Intellectual Stimulation, and Individual Consideration with the principles of transformative leadership from the view of the Qur'an.